Content validation of an activity-based therapy tracking tool in a community setting for people living with spinal cord injury or disease using cognitive debriefing interviews. - Anita Kaiser; Hanan Idd; Katherine Chan; Alexander Djuric; Sandi Marshall; Heather Cairns-Mills; Jennifer Leo; Kristin E Musselman (PLoS ONE)
Background Activity-based therapy (ABT) has shown promise as a viable therapeutic intervention to promote neurorecovery in people with spinal cord injury/disease (SCI/D). Tools that track the details of ABT sessions may facilitate the collection of data needed to inform best practice guidelines for ABT. Objective The purpose of this study was to evaluate the content validity of a prototype ABT tracking tool. Methods Nine clinicians and five individuals with SCI/D from three community-based ABT clinics in Canada used the prototype tracking tool over three ABT sessions and then participated in individual cognitive debriefing interviews. The interview guide was developed based on recommendations by Brod and colleagues for establishing content validity (i.e., appropriate, comprehensive, comprehensibility). Interviews were transcribed verbatim and analysed using deductive followed by inductive content analysis. Results Overall, the ABT tracking tool was found to have good content validity. Identified categories included: (1) Content validity of the ABT tracking tool. Participants found the tool to be comprehensive and appropriate for all levels and severities of injury. Recommendations to improve the tool included adding a comment section and additional parameters to each activity. (2) Facilitators of tool use, dissemination and implementation. Using the tool during rest breaks or after the session were suggested to maximize therapy time. Providing the tool as an app and offering education and training on use of the tool were highly recommended. Advertising through community clinics and social media may facilitate dissemination of the tool. (3) Barriers of tool use, dissemination and implementation. The paper format of the tool, added workload, learning curve and challenge to adopt a new documentation system were considered barriers to tool use. Conclusions The prototype ABT tracking tool was validated for content using cognitive debriefing interviews. Recommendations will be used to improve the tool and assist in dissemination and implementation efforts.